A novel luciferase-based assay for quantifying coronavirus-induced syncytia - Keisuke Oguma; Kenji Ogawa (Scientific Reports)
Abstract Coronaviruses can induce cell‒cell fusion that results in the formation of multinucleated syncytia through the interaction of viral spike proteins with host cell receptors. Quantifying syncytial formation is crucial for screening potential efficacious antiviral compounds. However, some traditional methods for syncytial quantification are often labor-intensive and limited by a low-throughput capacity. Therefore, we developed a novel high-throughput assay for the efficient quantification of syncytial formation induced by feline coronavirus (FCoV) and SARS-CoV-2. This assay, which is based on the split luciferase system, utilizes a split Gaussia luciferase (Gluc) system. In this system, fragments of Gluc are fused to the multimerizing Tau protein to reconstitute enzymatic activity upon cell fusion. In this study, the activity of the reconstituted luciferase was measured in 20 µL of culture medium to efficiently quantify syncytial formation induced by FCoV and SARS-CoV-2. Our findings demonstrate that this assay can accelerate the discovery of antiviral drugs that target coronaviruses.